Composition of periphyton attached in the stone substrate in the Salo River, Salo Village, Salo Districts, Kampar Regency - Simangunsong, Indra R.; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Periphyton is a group of aquatic microorganism that grew in the surface of natural substrates such as rock, wood, plants and aquatic animals. A research aims to understand the periphyton composition in the Salo River was conducted in April to May 2015. Sampling were conducted in 3 stations, they were in the upstream (St1), midstream (St 2), downstream (St 3), 4 times, once/ week. Results shown that there were 42 periphyton species present and they are belonged to 4 classes, namely Bacillariophyceae (28 species), Cyanophyceae (6 species), Chlorophyceae (7 species) and Dynophyceae (1 species). The abundance of periphyton in the upstream, midstream and downstream Salo River is significantly different, there were upstream (630 cell/cm2), midstream (1,499 cell/cm2), and downstream (4,545 cell/cm2) respectively. Periphyton abundance in the Salo River in general was around 630 – 4,545 cells /cm2.Keywords : Salo River, Periphyton, Composition